El Occidente bárbaro 400-1000 - Wallace-Hadrill, J. M. (John Michael); Santano Moreno, Bernardo; Rojas Gabriel, Manuel; Uzquiza González, José Ignacio (Madrid : Sílex ; Cáceres (España) : Universidad de Extremadura, Servicio de Publicaciones, 2014)
Professor Wallace-Hadrill traces the development of Western Europe from the dissolution of the late Roman Empire to the emergence, in the tenth century, of the individual states of medieval Europe.
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed November 11, 2016)
Keywords: Europe -- History -- 392-814.; Europe -- History -- 476-1492.; Electronic books